Investigation on Orange Peel: Derivatization of Isolated Cellulosic Material and Analysis of the Fatty Acids Composition - Islam, Md Rabiul; Muslim, Tanvir; Rahman, Md Azizur (Dhaka University Journal of Science, 2012)
Isolation of cellulosic material from the waste material, orange (Citrus sinensis) peel has been carried out. The isolated cellulosic material has been converted into its acetate ester. The acetate derivative has been characterized by titrimetric method and IR spectra. The fatty acid composition of the orange peel has also analyzed by GLC. Successful conversion of agro-waste into its acetate derivative and the fatty acid composition suggest an alternative use of this waste material. DOI: http://dx.doi.org/10.3329/dujs.v60i1.10341 Dhaka Univ. J. Sci. 60(1): 77-78 2012 (January)